Proceedings of the 2013 ACM International Joint Conference on Pervasive and Ubiquitous Computing 2013
DOI: 10.1145/2493432.2493500
|View full text |Cite
|
Sign up to set email alerts
|

Power harvesting from microwave oven electromagnetic leakage

Abstract: In this paper, we considered the possibility of using electricity harvested from the microwave field leaked from commercial microwave ovens. Our experimental results showed that the leakage received by a dipole antenna was about 0 dBm (1 mW) at a point 5 cm in front of the door. A rectenna consisting of a dipole antenna and charge pump can convert the leaked microwave energy into a DC current. When a microwave oven is operated for 2 min, 9.98 mJ of energy was harvested. We demonstrated that this energy is suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Even though they are mentioned here, there was no evidence that radiation from microwave ovens was detected in the measurements because of their distance from the sensing antenna. Other studies have shown that useful energy can be harvested from the leaked microwave field of commercial ovens, if the harvesting antenna is near the microwave oven door (5 cm) [18].…”
Section: Frequency Bandsmentioning
confidence: 99%
“…Even though they are mentioned here, there was no evidence that radiation from microwave ovens was detected in the measurements because of their distance from the sensing antenna. Other studies have shown that useful energy can be harvested from the leaked microwave field of commercial ovens, if the harvesting antenna is near the microwave oven door (5 cm) [18].…”
Section: Frequency Bandsmentioning
confidence: 99%
“…The strength of this microwave is up to -0.48 dBm, which is much stronger than that of Wi-Fi signal and therefore we can measure this leakage even from a distance [1]. In our previous work [1], we have shown that the leaked energy varies depending on the contents of the microwave oven and also the condition of these foods as shown in Figure 1. This can be attributed to the dielectric property of the substances, dielectric constant and dissipation factor.…”
Section: Introductionmentioning
confidence: 89%
“…P. Sebastian et al proposed a food intake recognition method by investigating the acoustics of chewing different kinds of food [9]. Actually, research on the power leakage of the microwave oven has been conducted on energy harvesting [1] and WLAN network communication quality [10]. In this paper, we explore the usage of microwave oven leakage for food recognition.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to TV and mobile communication signals, wireless LAN hotspots and smart meters used in residential and industrial areas have inundated the air with electromagnetic waves in different frequencies with in the HF, VHF and UHF bands. While most of the ambient microwaves are communication signals for voice, video and data communication and leakage from home appliances, they can also be used as a pervasive source of power in powering large scale, wireless and wired sensors for a range of applications such as structural, environmental and human health monitoring [1] [2].Wireless power transfer/harvesting has been the focus of the research community in recent years. This technology already has been applied in near and far field RFIDs for logistics under the ISO 18000 standards, and for powering smart-phones under the NFC-based Qi standard.…”
Section: Introductionmentioning
confidence: 99%